Адміністративна відповідальність за мобінг: перспективи внесення змін до законодавства України - Ковальова, Марина; Божук, Ірина; Kovalyova, Maryna; Bozhuk, Iryna (ЗУНУ, 2020)
Досліджено теоретико-практичні аспекти та юридичні особливості мобінгу як суспільного явища. Наведено думки різних науковців щодо визначення поняття та ознак мобінгу. Зазначено, що українське суспільство потребує негайного врегулювання цієї проблеми, тому дослідникам варто глибше дослідити цю тему з юридичної точки зору. Вказано, що законодавство деяких зарубіжних країн унормувало заборону мобінгу (психологічного тиску) на робочому місці. Сформульовано висновок, що в інших країнах захист гідності працівника під час трудової діяльності є такою самою важливою складовою, як і інші умови праці. Досвід розвинутих країн необхідно вивчати та запроваджувати в Україні з метою покращення умов праці працівників, у тому числі через створення комфортної психологічної атмосфери та розробки механізму відповідальності винних осіб. Проаналізовано основні аспекти законопроєкту № 4306 та надано йому позитивну оцінку. Закцентовано увагу на необхідності призначення адміністративної відповідальності за мобінг. The article examines the theoretical and practical aspects and legal features of mobbing as a social phenomenon. The article presents the opinions of various scientists on the definition of the concept and characteristics of mobbing. It is noted that the Ukrainian society demands an immediate settlement of this problem, so scientists should study this topic more deeply from a legal point of view. The purpose of the article is to study the essence and content of the concept of mobbing, to analyze its legal features, to describe the main aspects of the legislation of some foreign countries to combat and prohibit mobbing, as well as to identify its application. The article pays considerable attention to the study of topical issues of legal regulation of prohibition and counteraction to mobbing in the legislation of Ukraine, prospects for the introduction of administrative liability for mobbing through the adoption of the bill №4306, as well as identifying its positive and negative aspects. It is stated that the legislation of some foreign countries has regulated the prohibition of mobbing (psychological pressure) in the workplace. It is concluded that in other countries the protection of the dignity of the employee during employment is as important a component as other working conditions. The experience of developed countries needs to be studied and implemented in Ukraine in order to improve the working conditions of workers, including through the creation of a comfortable psychological atmosphere and the development of a mechanism for liability of perpetrators. The main aspects of the draft law №4306 were analyzed and given a positive assessment. Emphasis is placed on the need to assign administrative responsibility for mobbing. It should be emphasized that the chosen topic remains insufficiently studied by domestic scientists and needs a deeper analysis for its regulation.
Administrative responsibility for mobbing: prospects for changing the legislation of Ukraine
Keywords: мобінг; булінг; цькування; адміністративна відповідальність; психологічний тиск; психологічне насильство; зарубіжний досвід; mobbing; bullying; harassment; administrative liability; psychological pressure; psychological violence; foreign experience